Profil Keterampilan Berpikir Kritis Siswa SMP Negeri 1 Juwangi pada Pembelajaran IPA - Novita Widhi Widyapuraya; Ayu Lilis Suryana; Suyanta Suyanta; Insih Wilujeng (Postgraduate, University of Mataram, 2023)
The purpose of this study is to determine the profile of the critical thinking skills of junior high school students in science learning. This type of research is descriptive quantitative with purposive sampling techniques with the subject in this study, namely grade VII students at SMP Negeri 1 Juwangi. The result of the study is that each indicator of critical thinking skills has different results. The interpreting indicator has a value of 67,96 including the enough category, the analyze indicator has a value of 47,65 belonging to the low category, the evaluating indicator has a value of 66,40 belonging to the enough category, the indicator concludes to have a value of 53,12 belongs to the low category, and the explaining indicator has a value of 48,43 belonging to the low category. the average critical thinking skills of learners belong to the low category with a score of 56,57. The low critical thinking skills are caused when the learning process is still conventional so that it is only centered on the teacher and also not optimal learning activities that can improve students' critical thinking skills. Based on the results of the study, it is hoped that researchers can then develop learning tools that can improve students' critical thinking skills in science learning in junior high schools